Factors Affecting the Liquidity Risk of Commercial Banks in Nepal - Niroula, Ballav; Gnawali, Bindu (Indonesian Business Review, 2024)
Level liquidity is an important factor that helps the growth and survival of commercial banks. This research aims to show the factor affecting the liquidity risk of commercial banks in Nepal. The panel data were used to analyze and find the results from the period 2017 to 2021. Secondary data are collected from the annual report of commercial banks. Banks’ internal factors bank size, capital adequacy ratios, non-performing loans, return on assets, return on equity, and external factor gross domestic product was used as independent variables. The dependent variable of the research is the liquidity ratio. A descriptive research design has been used to explain the data. A convenient sampling technique was used to select the 16 commercial banks as a sample from the population of 26 banks. Various statistical methods are used to describe the data and to find the result from the 80 observations. The result shows that there is a significant and negative relationship between bank size and non – performing loans with the liquidity of commercial banks in Nepal, but GDP, ROA, and ROE have significant positive effects on liquidity. To maintain the liquidity level commercial banks, need to minimize the non – performing loans. It is crucial to take into account the size of the bank, the nature of the crisis, the regulatory environment, the interconnection of the financial sector, market perception, and contagion risk when large banks have a negative impact on liquidity. Knowing these elements will make it easier to find suitable answers to the liquidity issue and lessen the effects it has on the larger financial system.